Usulan Perbaikan Tata Letak Bagian Proses Produksi pada PT. X Menggunakan Metode SLP dan Craft - Fidea Rahma; Andika Rendra Al-Ghoffard; Firly Arviani Yasla; Tiaradia Ihsan (SENTRI: Jurnal Riset Ilmiah, 2026)
PT X is a company engaged in the natural extract industry that still faces facility layout problems in its production process, particularly in the simplisia extract production area. The existing facility layout is not arranged according to the production process sequence and the degree of closeness between departments, resulting in inefficient material flow, long material handling distances, and increased material handling costs. This study aims to redesign the production facility layout to improve material flow efficiency and minimize material handling costs. The methods used are Systematic Layout Planning (SLP) to analyze the closeness relationships between departments through the Activity Relationship Chart (ARC) and Activity Relationship Diagram (ARD), and the Computerized Relative Allocation of Facilities Technique (CRAFT) to optimize the layout quantitatively using a From-To Chart with the support of WinQSB software. The results indicate that the proposed layout improves the production process flow and reduces material handling distance and cost compared to the initial layout. The combination of SLP and CRAFT is proven to be effective in producing a more systematic, efficient, and economical production facility layout, thereby supporting increased productivity and operational efficiency at PT X.